Fábulas de Esopo e Millôr Fernandes: uma análise contextual - Farencena, Gessélda Somavilla (Linguagens & Cidadania, 2017)
In this work, sharing the functional view of language as that is instantiated in text, it is always considered in use and therefore, inserted into some context and both - text and context - influence each other, are analyzed 14 fables: seven originally attributed to Aesop and seven versions revisited by Millôr Fernandes. Thus, we aimed to verify the Contextual Configuration (CC) which involves both the fables and the fabulists. For this purpose, from Thompson & Thetela (1995), we describe the situational context making the distinction of interaction between author/reader and author-in the-text/reader-in the-text. Based on Halliday (1989), we describe the context of situation in terms of three variables. These analysis, in relation to the social contexts in which the fables were produced, the results indicated similarities and differences concerning the situations of oppression experienced by Aesop as a slave and the ones lived by Millôr Fernandes during the Brazilian Military Dictatorship. On the other hand, the nature and consequences of this oppression are distinct in the context of each author. Regarding the situational variables, the results showed that there are similarities concerning in characters, situations presented and mode, but though, they differ as to the rhetorical function.